1993
DOI: 10.1002/gcc.2870070106
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of chromosome 11 and of 14q sequences in neuroblastoma

Abstract: Restriction fragment length polymorphism (RFLP) analysis carried out on 45 primary neuroblastomas showed deletion of chromosome 11 sequences in 12 of 37 (32%) informative cases. Both 11p and 11q probes were informative in seven tumors; loss of all of chromosome 11, of only 11p sequences, and of only 11q sequences was observed in 4, 1, and 2 tumors, respectively. A cytogenetic abnormality involving translocation of chromosome arm 11q to chromosome arm 1p was observed in a primary tumor. Deletion of 14q was obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
45
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(49 citation statements)
references
References 37 publications
(48 reference statements)
4
45
0
Order By: Relevance
“…The frequently observed GGP tumors are as follows: GGP1a tumors with both 1p loss and MYCN amplification and GGP3s tumors with 11q loss but without MYCN amplification. The former may belong to a typical MYCN-amplified neuroblastoma (White et al, 1995) with a 5-year cumulative survival rate of 42% in our series, whereas the latter to the so-called intermediate type tumor (Srivatsan et al, 1993;Attiyeh et al, 2005) with the rate of 75%. In GGP tumors, it is obvious that MYCN amplification has the most powerful impact on the patient prognosis.…”
Section: Discussionmentioning
confidence: 61%
“…The frequently observed GGP tumors are as follows: GGP1a tumors with both 1p loss and MYCN amplification and GGP3s tumors with 11q loss but without MYCN amplification. The former may belong to a typical MYCN-amplified neuroblastoma (White et al, 1995) with a 5-year cumulative survival rate of 42% in our series, whereas the latter to the so-called intermediate type tumor (Srivatsan et al, 1993;Attiyeh et al, 2005) with the rate of 75%. In GGP tumors, it is obvious that MYCN amplification has the most powerful impact on the patient prognosis.…”
Section: Discussionmentioning
confidence: 61%
“…Besides cervical cancer, LOH studies have implicated chromosome 11q13 in a number of human tumors including breast, head and neck, neuroblastoma and endocrine tumors (Srivatsan et al, 1993;Zhuang et al, 1995;Chakrabarti et al, 1998;Venugopalan et al, 1998;Tanaka et al, 1998). Recently, the minimal 11q13 deletion for a nasopharyngeal carcinoma tumor suppressor gene was localized to a 1.8 Mb interval that overlapped with the 300 kb deletion observed in cervical cancer (Cheng et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…We cloned the human KIF1B-b gene from a region that was homozygously deleted in the NB cell line, NB-1. We physically mapped the KIF1B-b gene to 1p36.2, telomeric to D1S244 between WI-14873 and stSG 14169, within the commonly deleted region of NB (Schwab et al, 1996;Srivatsan et al, 1993;Maris and Matthay, 1999). Using two KIF1B-b polymorphic markers and two microsatellite markers in both sides of KIF1B-b, we found that the incidence of AI in the KIF1B-b gene was slightly higher than in the D1S244 and D1S1350 loci.…”
Section: Discussionmentioning
confidence: 99%
“…One of these is ampli®cation of the MYCN gene that is associated with a poor prognosis in NB (Seeger et al, 1985;Hayashi et al, 1989;Brodeur and Fong, 1989). Another is the loss of heterozygosity (LOH) at the 1p (Fong et al, , 1992Takita et al, 1995;Schwab et al, 1996), long arm of chromosome 11 (11q) (Srivatsan et al, 1993) and 14q (Srivatsan et al, 1993;Suzuki et al, 1989) in NB. In addition to those mentioned above, we recently found a LOH at 2q, 9p and 18q (Takita et al, 1995(Takita et al, , 1998.…”
Section: Introductionmentioning
confidence: 99%